Tree species diversity impacts average radial growth of beech and oak trees in Belgium, not their long-term growth trend - Astrid Vannoppen; Vincent Kint; Quentin Ponette; Kris Verheyen; Bart Muys (Forest Ecosystems, 2019)
Abstract Background Environmental change has resulted in changes in forest growth in Europe during the last century. This has consequences for the products and services delivered by forest. Mixing tree species is often proposed as a strategy to deal with the consequences of climate change. Diversifying forests is believed to result in higher productivity and increased growth stability. Tree species diversity is therefore expected to affect long-term trends in tree radial growth. However, this has not yet been studied. In this paper we study the effect of diversity on the radial growth and its long-term trends for beech and oak trees growing along a gradient of tree species diversity in the loamy region of central Belgium (from monocultures to mixed forests patches up to three species). Results We found that beech trees have a higher radial growth whereas oak trees have a lower one when growing in mixtures. The contrasting diversity-productivity relationship observed for beech and oak is in agreement with their ranking in shade tolerance, where oaks suffer increased competition in mixed oak patches. Overall, in monocultures and mixtures, an increasing radial growth trend of + 2% for the period 1927–2015 and 21% for the period 1899–2015 was found for beech and oak, respectively. Tree species diversity did not alter the shape of this detected long-term radial growth trend. Nevertheless, for oak a lower year-to-year variability in radial growth is found in mixtures indicating a higher resilience. Conclusion We conclude that diversity impacts the average radial growth and its variability (only in the case of oak) but not the shape of the long-term trend in radial growth of beech and oak trees growing in the loamy region of central Belgium.